ДУХLESS: повесть о ненастоящем человеке / Сергей Минаев - Минаев Сергей Сергеевич (Современная проза, 2006)
Экземпляры: ф.11 (20190429) / Инвентарный номер: 59615 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44